Prevalence of Macroprolactinemia in People Detected to Have Hyperprolactinemia - Sharma, Lokesh Kumar; Dutta, Deep; Sharma, Neera; Kulshreshtha, Bindu; Lal, Sandhya; Sethi, Ritika (Journal of Laboratory Physicians, 2021)
Background Macroprolactinemia is an analytic laboma encountered as a part of prolactin assay. No data are available on the burden of macroprolactinemia in Indians. This study aimed to determine the prevalence and predictors of macroprolactinemia among people with hyperprolactinemia.Methods Consecutive patients detected to have serum prolactin > 18 ng/mL as per the upper reference limit were further screened for macroprolactin by post-polyethylene-glycol (PEG)-precipitation test. Macroprolactinemia was defined as post-PEG recovery of prolactin < 40%.Results The four most common underlying etiologies for the testing of hyperprolactinemia were polycystic ovary syndrome (n = 402; 32.71%), pituitary adenomas (n = 318; 25.87%), drug-induced hyperprolactinemia (n = 224; 18.23%), and infertility (n = 126; 10.25%). A total of 1,229 patients (male:female = 191:1038) having mean age 30.46 ± 10.14 years had hyperprolactinemia, of which 168 (13.7%) were diagnosed to have macroprolactinemia. Macroprolactinemia was significantly higher in females than males (15.03 vs. 6.28%; p < 0.001). Age quartile-based analysis revealed no difference in occurrence of macroprolactinemia. Only 34 patients (2.76%) with macroprolactinemia (< 40% recovery of prolactin post-PEG precipitation) had raised prolactin levels after recovery. These patients primarily had underlying pituitary pathology.Conclusion Macroprolactinemia is not uncommon in people being tested for hyperprolactinemia. We should not hesitate to screen for macroprolactinemia in patients who have incidentally been detected to have hyperprolactinemia.
Keywords: macroprolactin; prolactin; macroprolactinemia; pituitary